On the effect of local torsion on the electromechanical properties of armchair boron nitride nanoribbons. (3rd June 2022) - Sadeghi, R.; Yaghobi, M.; Niazian, M. R.; Ramzanpour, M. A.
Abstract : Similar to graphene nanoribbons, boron nitride nanoribbons are prone to twist intrinsically. Hence, investigating the effect of local torsion on the electromechanical properties of boron nitride nanoribbons (9-cells) is of great importance. By using the density functional theory in combination with the non-equilibrium Green's function method, the effect of local torsion on the structural evolution and electrical transport of armchair boron nitride nanoribbons is investigated here. In addition, the electrical transport, current–voltage and Local density of state (LDOS) are studied. It is shown that local twist can change the transport properties of the boron nitride nanoribbons significantly. The current at a given bias can switch on/off or change many times with twist angle, which is related to twist-induced changes in electronic structures of boron nitride nanoribbons. The results of the current work can provide a valuable guideline for design and implementation of boron nitride nanoribbons in nanoelectromechanical systems and devices. GRAPHICAL ABSTRACT: UF0001